Mortality and its predictors among patients with Guillain–Barré syndrome in the intensive care unit of a low-income country, Ethiopia: a multicenter retrospective cohort study - Bayu, Habtu Tsehayu; Demilie, Atalay Eshetie; Molla, Misganew Terefe; Kumie, Fantahun Tarekegn; Endeshaw, Amanuel Sisay (Frontiers in Neurology, 2024)
Background Guillain–Barré syndrome (GBS) is a rare autoimmune disease that affects the peripheral nervous system. It is characterized by the destruction of nerves involved in movement. This condition can lead to transient pain, changes in temperature and touch sensations, muscle weakness, loss of sensation in the legs and/or arms, and difficulty swallowing or breathing. Published data on the outcomes of critical care for patients with GBS are extremely scarce in Africa, particularly Ethiopia. Therefore, this study aimed to assess mortality and its predictors among patients with GBS in the intensive care unit (ICU) of specialized hospitals in Ethiopia, a low-income country. Materials and methods This retrospective cohort study was conducted at the Tibebe Ghion Specialized Hospital and the Felege Hiwot Comprehensive Specialized Hospital in Bahir Dar, Ethiopia, from 1 January 2019 to 30 December 2023. Data were collected in the medical record rooms. Cox regression analysis was performed to identify the predictors of mortality among GBS patients in the ICU. The crude and adjusted hazard ratios (AHRs) and 95% confidence intervals (CIs) were calculated using bivariable and multivariable Cox regression models. A p-value of <0.05 was considered statistically significant. Results Of 124 GBS patients admitted to the ICU, 120 were included in the final analysis. During the follow-up, there were 23 (19.17%) deaths. The overall incidence rate of death was 1.96 (95% CI: 1.30, 2.95) per 100 person-days of observation. Traditional medicine (AHR = 3.11, 95%: 1.12, 16.70), COVID-19 infection (AHR = 5.44, 95% CI: 1.45, 73.33), pre-ICU cardiac arrest (AHR = 6.44, 95% CI: 2.04, 84.50), and ICU readmission (AHR = 4.24, 95% CI: 1.03, 69.84) were identified as the independent predictors of mortality. Conclusion The mortality rate among GBS patients admitted to the ICU was high. Traditional medicine, COVID-19 infection, pre-ICU cardiac arrest, and readmission to the ICU were the significant predictors of mortality. Conducting large-scale studies with a prospective design in the future would yield more robust evidence.